Assisting Women in Ranon Village in Enhancing Capacity to Untilize Home Gardens for Nutritious Food - Siti Dzulfirda Nivea Cholis; Amira Firdausi; Ida Rochmawati (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
Food security and low nutrition literacy remain critical challenges in rural areas, particularly in Ranon Village. Many household yards are underutilized, and housewives have limited knowledge about processing local food sources such as water spinach (kangkung), lemongrass, and ginger into nutritious meals. This community service program aimed to enhance the capacity of rural women especially members of the Family Welfare Movement (PKK) and Posyandu cadres in utilizing homegrown produce to prepare healthy and nutritious food. The program employed a Participatory Action Research (PAR) approach, engaging the community in all stages from problem identification to evaluation. Activities included nutrition education and cooking demonstrations using local ingredients, such as the preparation of water spinach brownies. Results showed that 80% of participants had a good understanding of the nutrition material and were able to apply the skills to process healthy food from their gardens. The program successfully improved participants’ nutritional literacy and food preparation skills, while also promoting productive use of home gardens for household food security. This participatory approach proved effective in raising awareness and encouraging sustainable healthy eating behaviors at the household level.